Long day's journey into night - O'Neill, Eugene; Lumet, Sidney Hepburn, Katharine Richardson, Ralph Robards, Jason (Yale University Press; London, 2019)
Eugene O'Neill's autobiographical account of his turbulent family life is brought to the screen with an overpowering wealth of talent. Katharine Hepburn as the mother - lonely, ravaged by narcotics and frightened by a world with which she cannot cope. Ralph Richardson as the alcoholic father, a miser embittered by his expired career. Jason Robards as the tortured older brother, a failure to everyone including himself. And Dean Stockwell as the budding writer struggling with his craft... and a family that exists in name only